A method for preparing solid-state battery electrode and solid-state electrolyte membrane
By using the hyperdigical function polymer as a binder, the high -temperature mixing and screw extrusion process preparation electrodes and solid electrolytes are used to solve the problem that traditional craftsmanship is difficult to meet the high density and good cycle performance of all solid -state batteries. Low -cost battery performance improvement.
Patent Information
- Application Number
- CN202410154740.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-02-04
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-02-04
AI Technical Summary
Traditional wet coating processes are difficult to meet the demands of all-solid state batteries for high density, good cycle performance and low cost, and there is consistency and ionic conduction path of fibrotic binders and crosslinked polymers used in the dry process. question.
The use of hyperdigyal function polymers as a binder and prepare electrodes and solid electrolytes through high temperature mixing and screw extrusion process to ensure the high density and good circulation performance of the electrode and solid electrolyte.
The high density and good cycle performance of the electrode and solid electrolyte film are realized, and the multiplier and cycle performance of the all -solid -state battery are improved, while reducing production costs and increasing process consistency.
Smart Images

Figure CN117895090B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a battery manufacturing process, and in particular to a method for preparing a solid-state battery electrode and a solid-state electrolyte membrane. Background Art
[0002] In recent years, with the rapid development of new energy vehicles, the market demand for battery capacity and safety performance has become increasingly higher. With the continuous development of battery technology, the development of all-solid-state batteries with high energy density and high safety has received widespread attention. All-solid-state batteries use solid electrolytes as a way of ion conduction. There is no fluid liquid in the battery, which is safer and more reliable than electrolyte batteries. For all-solid-state batteries made of new solid materials, there are certain changes in the demand for electrodes, solid electrolyte membranes, and batteries, as well as in the production and manufacturing processes.
[0003] Because there is no liquid in the all-solid-state battery, the gaps inside and on the interface of the electrode and diaphragm are not filled with liquid, and the ion conduction path relies entirely on solid contact, so the electrodes and solid electrolyte membranes in the all-solid-state battery require a very high density to increase the contact area between the solid particles, thereby reducing the internal resistance of the battery and improving the battery's rate performance. In addition, because the active materials have a certain expansion and contraction effect during the operation of the battery, the battery electrodes and solid electrolyte membranes, including the current collector structures, need to maintain contact during the expansion and contraction process to reduce capacity attenuation and maintain good cycle performance.
[0004] The traditional battery coating roller pressing process uses a large amount of solvent during wet coating, and many holes will be obtained after coating and drying. The initial porosity is very large, and the substrate rolling force is limited, and it is difficult to achieve high density after rolling. The high porosity of this wet process is very suitable for traditional electrolyte batteries, but it is not suitable for the needs of all-solid-state batteries. Compared with the wet preparation of electrodes and solid electrolyte membranes, the dry preparation method does not use solvents, which can significantly improve the density of electrodes or solid electrolyte membranes and is more suitable for the needs of all-solid-state batteries. The main dry electrode processes currently disclosed, such as CN202311187835.8, CN202310962128.5, CN202310886118.8, etc., all use polytetrafluoroethylene as a fiberizing binder. The fiberizing binder has a fiberizing limit, and the tensile changes in all directions during the extension process are inconsistent, and the deformation performance deteriorates nonlinearly, which is not conducive to the stability and consistency of the production process. However, CN202111325320.0 uses linear polymer cross-linking as a binder. The positive electrode prepared with this cross-linked binder has strong rigidity and cannot maintain material contact during the expansion and contraction of the electrode materials during battery cycling, which is not conducive to the overall cycling performance of the battery.
[0005] Analyzing the requirements of all-solid-state batteries for electrodes and solid electrolyte membranes, the final effect mainly has the following requirements:
[0006] 1. High density, close contact between solid particles, large effective contact area and high ion conductivity.
[0007] 2. There is a certain elastic contact between the particles to ensure that they do not separate after expansion and contraction, and the capacity is not lost.
[0008] 3. The ion conduction is smooth, and there is no insulator covering to interrupt the ion path.
[0009] Considering the mass production and industrialization of all-solid-state batteries, the following requirements are also required in terms of process:
[0010] 4. The process is simple, the amount of auxiliary materials is low, the cost is low, and it is economical and environmentally friendly.
[0011] 5. The process has strong repeatability, simple standards, good consistency and reliability.
[0012] The current traditional electrode wet coating electrode production process mixes the active material in a slurry of binder and solvent, which requires a large amount of volatile solvent and has high auxiliary material cost, which does not meet requirement 4. At the same time, the large number of voids caused by solvent evaporation still have a porosity of about 20% after rolling, which does not meet requirements 1 and 3. The production of traditional electrodes usually uses binders such as polyvinylidene fluoride PVDF, which has a high degree of crystallinity and is rigid as a whole, which does not meet requirement 2.
[0013] In summary, the wet coating process is not suitable for the production of all-solid-state batteries, and the dry process is more suitable for the production of all-solid-state batteries.
[0014] The dry process of using polytetrafluoroethylene (PTFE) as a fiberized binder is currently used. Due to the tensile limit and anisotropy of the PTFE material, it is difficult to evaluate the state under different shear conditions, and the consistency of the process itself is difficult to control, which does not meet requirement 5. Other methods that use ordinary cross-linked polymers as binders are simpler in terms of process than fiberized binders, but generally cross-linked polymers are more rigid and hinder the transfer path of ions in the battery, and cannot fully meet requirements 2 and 3. Summary of the invention
[0015] In order to solve the above technical problems, the present invention provides a method for dry-process preparation of electrodes and solid electrolyte membranes using hyperbranched functional polymers as binders. By utilizing the low glass transition temperature, high temperature fluidity and special properties of ionic conductivity of the hyperbranched functional polymers provided by the present invention, the electrodes and solid electrolyte membranes prepared by the method have high density, and continuous contact between solid materials can be ensured during the cycle process, thereby improving the rate and cycle performance of all-solid-state batteries.
[0016] As one of the objects of the present invention, the present invention provides a method for preparing a solid electrolyte membrane, comprising the following steps:
[0017] (1) adding a solid electrolyte material, a polymer binder and a plasticizer into a mixer in proportion, and obtaining a uniform mixture by high-temperature mixing, wherein the solid electrolyte material accounts for 85% to 98% by volume; the polymer binder accounts for 2% to 10% by volume; the plasticizer accounts for 0% to 5% by volume; and the glass transition temperature of the polymer binder is lower than -30°C;
[0018] (2) Extruding the mixed material through a screw and then rapidly cooling it to obtain an independent self-supporting solid electrolyte membrane; the extrusion temperature is not less than 80° C., and the product porosity is less than 5%.
[0019] As one of the objects of the present invention, the present invention provides a method for preparing a solid-state battery electrode, comprising the following steps:
[0020] (1) adding an electrochemical functional material, a polymer binder and a plasticizer into a mixer in proportion, and obtaining a uniform mixture by high-temperature mixing, wherein the volume proportion of the electrochemical functional material is 83%-98%; the volume proportion of the polymer binder is 2%-10%; the volume proportion of the plasticizer is 0%-5%; and the glass transition temperature of the polymer binder is lower than -30°C;
[0021] (2) Extruding the mixed material into sheets through a screw, compounding the sheets on a current collector and calendering to obtain a final product; wherein the extrusion temperature is not less than 80° C. and the porosity of the product is less than 5%.
[0022] Preferably, the polymer binder is a hyperbranched functional polymer prepared by the following steps:
[0023] Step 1: using a raw material with multiple nucleophilic sites to react with a crosslinking agent to generate a branched donor polymer;
[0024] Step 2: The nucleophilic site of the donor polymer undergoes a Michael addition reaction to obtain a hyperbranched polymer;
[0025] Step 3: Heat and mix the above hyperbranched polymer and metal salt at 40° C. until the salt is completely dissociated.
[0026] Preferably, the nucleophilic site of the raw material in step 1 is one or more of a hydroxyl group, an amino group, and a thiol group. Preferably, the raw material is one or more of a polyol, 2,3-dimercaptopropanol, sorbitol, pentaerythritol, inositol, dipentaerythritol, pentaerythritol, amino alcohol, polyethyleneimine, cysteine, and dithiothreitol.
[0027] Preferably, the crosslinking agent is a multifunctional crosslinking agent, preferably a dialdehyde, epichlorohydrin, diisocyanate, diacrylate, diglycidyl ether, dibromide, dichloride or divinyl;
[0028] Preferably, the metal salt added in step three is one or more of lithium salt, sodium salt, magnesium salt and aluminum salt.
[0029] Preferably, the plasticizer is TEP, DOP or BET;
[0030] Preferably, the electrochemical functional material may include a solid electrolyte material, positive and negative electrode active materials and a conductive material;
[0031] The positive and negative electrode active materials include lithium ion battery positive electrode materials, sodium ion battery positive electrode materials, lithium battery negative electrode materials and sodium battery negative electrode materials;
[0032] The conductive material may be any one or more of conductive carbon black, graphene, and carbon nanotubes.
[0033] Preferably, the solid electrolyte material includes any one or more of polymers, oxides, sulfides, halides, and ordered mesoporous polymer solid electrolytes; including but not limited to polyethylene oxide PEO, lithium lanthanum zirconium oxide LLZO, lithium germanium phosphorus sulfur LGPS, and lithium indium chloride Li3InCl6.
[0034] Preferably, the positive electrode material of the lithium-ion battery is LiMn2O4, LiCoO2, LiFePO4, LiNi x Co y Mn z O2、LiNi x Co y Al z One or more of O2 and lithium-rich compounds, wherein x+y+z=1;
[0035] The positive electrode material of the sodium ion battery is one or more of sodium metal oxide, Prussian material, and polyanion compound;
[0036] The negative electrode material of the lithium battery is one or more of graphite, silicon, lithium titanate, silicon dioxide, tin, indium, and hard carbon;
[0037] The negative electrode material of the sodium battery is one or more of graphite, soft carbon, hard carbon, and transition metal oxides.
[0038] Preferably, when manufacturing the positive electrode sheet, the substrate current collector can be aluminum foil, perforated aluminum foil, carbon-coated aluminum foil or composite aluminum foil; when manufacturing the negative electrode sheet, the substrate current collector can be copper foil, perforated copper foil, composite copper foil or carbon-coated copper foil.
[0039] Preferably, when preparing the positive and negative electrode sheets of the solid-state battery, the volume of the positive and negative electrode active materials accounts for 60%-75%; the volume of the solid electrolyte material accounts for 23%-38%; the volume of the conductive agent accounts for 0%-5%; the volume of the polymer binder accounts for 2%-10%; and the volume of the plasticizer accounts for 0%-5%.
[0040] As one of the objects of the present invention, the present invention provides an electrochemical device comprising a solid electrolyte membrane or a solid battery electrode prepared by the above method.
[0041] The hyperbranched polymer binder prepared by the present invention obtains a large number of polar functional groups through addition. The polymer has high dielectric properties, can help dissociate metal salts and provide channels for ion transmission. The high crystallinity of traditional polymers limits the movement and deformation of polymer segments. The hyperbranched polymer binder prepared by the present invention has a glass transition temperature below -30°C and has a large number of amorphous regions when the battery is working, which makes the ion transmission capacity in the network stronger, and the room temperature ion conductivity is 10 -5 -10 -3 S / cm, helping solid-state batteries to charge and discharge faster. The hyperbranched polymer binder has a high molecular weight and extremely high electrochemical stability, and can adapt to working in positive and negative electrode materials without decomposition and other side reactions.
[0042] The dry electrode and solid electrolyte membrane prepared by the present invention use hyperbranched polymer as a binder. In the dry process, the binder is in a molten state as a whole. The electrode and the solid electrolyte membrane are extruded under pressure, and the density is very high, the porosity is less than 5%, and the solids are in close contact, which can improve the ion transmission speed therein. The particles and the binder are evenly distributed in the electrode or solid electrolyte membrane, which is conducive to the industrialization of the process. The branched polymer binder used in the present invention has a certain elasticity during the battery operation process, can adapt to the expansion and contraction of the active material and the electrode during the battery charging and discharging process, and is conducive to improving the cycle performance and capacity retention rate of the solid-state battery. The process conditions are simple and suitable for the application of various types of new solid-state batteries such as lithium batteries, sodium batteries, and magnesium batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] Figure 1 is the reaction equation of the hyperbranched polymer binder of Example 1;
[0044] Figure 2 is the NMR spectrum of the hyperbranched polymer binder of Example 1;
[0045] Figure 3 This is a process flow chart for preparing a lithium cobalt oxide positive electrode sheet in Example 3;
[0046] Figure 4This is a schematic diagram of the structure of the lithium cobalt oxide positive electrode sheet prepared in Example 3, wherein 101 is a lithium cobalt oxide mixture, and 102 is an aluminum foil current collector;
[0047] Figure 5 This is a SEM image of the lithium cobalt oxide positive electrode sheet prepared in Example 3;
[0048] Figure 6 This is a schematic diagram of the structure of preparing a double-sided graphite negative electrode sheet in Example 5, wherein 100 is a release film, 103 is a graphite mixture, and 104 is a carbon-coated copper foil current collector;
[0049] Figure 7 Schematic diagram of the structure of the LGPS solid electrolyte membrane prepared in Example 6, wherein 100 is a release film and 105 is a LGPS mixture;
[0050] Figure 8 This is the EIS AC impedance diagram of the LGPS solid electrolyte membrane prepared in Example 6.
[0051] Fig. 9 This is a comparison chart of the all-solid-state battery cycles prepared in Example 9 and Comparative Example 3. DETAILED DESCRIPTION
[0052] Example 1
[0053] This embodiment discloses a method for preparing a hyperbranched polymer binder:
[0054] Using 2-amino-2-(hydroxymethyl)propane-1,3-diol as the starting material containing multiple nucleophilic sites, 0.5 mol of 2-amino-2-(hydroxymethyl)propane-1,3-diol was first added to 200 ml of N,N-dimethylformamide (DMF) solvent. The mixture was heated to 80°C and stirred to completely dissolve 2-amino-2-(hydroxymethyl)propane-1,3-diol.
[0055] 1,2-bis(oxirane-2-ylmethoxy)ethane was used as a crosslinking agent. 0.5 mol of 1,2-bis(oxirane-2-ylmethoxy)ethane was slowly added into the above completely dissolved mixed solution using a peristaltic pump, and 10 g of potassium carbonate was added as a catalyst. Under the protection of inert gas, the reactants were allowed to react continuously at 100°C. 2-amino-2-(hydroxymethyl)propane-1,3-diol and 1,2-bis(oxirane-2-ylmethoxy)ethane under the action of the catalyst underwent nucleophilic ring-opening addition to form a branched polymer A. When the color of the solution no longer changed, the DMF solvent in the above mixture was removed by adding water and rotary evaporation, and the polymer A was separated and purified.
[0056] The purified polymer A is placed in a mixed solvent of 240 g tetrahydrofuran and 40 g methanol and heated at 30°C to dissolve. 5 mol of acrylonitrile is slowly dripped into the above solvent, 10 g of cesium carbonate is added as a catalyst, and the reaction temperature is controlled to cause Michael addition reaction. After the reaction continues for 24 hours, excess dilute hydrochloric acid is added to neutralize the catalyst. After filtering the mixed solution, the catalyst, solvent, and excess reactants are removed by rotary evaporation to obtain a colloidal branched polymer B. The glass transition temperature of the polymer B is -40°C.
[0057] The polymer B and LiTFSI salt were mixed in a ratio of 100:20, and all lithium salts were dissolved in the polymer at 80° C. to obtain a final hyperbranched polymer binder.
[0058] The reaction equation for the synthesis of the above hyperbranched binder polymer is shown in the attached figure. Figure 1 As shown, the NMR spectrum is Figure 2 shown.
[0059] Example 2
[0060] This embodiment discloses a method for preparing a hyperbranched polymer binder:
[0061] Using sorbitol as the starting material containing multiple nucleophilic sites, 0.5 mol of sorbitol was first added to 200 ml of N,N-dimethylformamide (DMF) solvent, and the mixture was heated to 60° C. and stirred to completely dissolve the sorbitol.
[0062] 1,2-bis(oxirane-2-ylmethoxy)ethane was used as a crosslinking agent. 0.5 mol of 1,2-bis(oxirane-2-ylmethoxy)ethane was slowly added into the above completely dissolved mixed solution using a peristaltic pump, and 5 g of potassium hydroxide was added as a catalyst. Under the protection of inert gas, the reactants were allowed to react continuously at 100°C. Sorbitol and 1,2-bis(oxirane-2-ylmethoxy)ethane under the action of the catalyst underwent nucleophilic ring-opening addition to form a branched polymer A. When the color of the solution no longer changed, water was added and the DMF solvent in the above mixture was removed by vacuum rotary evaporation to separate and purify the polymer A.
[0063] The purified polymer A is placed in a mixed solvent of 240 g tetrahydrofuran and 40 g ethanol, and heated at 30°C to dissolve. 50 g acrylonitrile is slowly dripped into the above solvent, 10 g cesium carbonate is added as a catalyst, and the reaction temperature is controlled to cause Michael addition reaction. After the reaction continues for 24 hours, excess dilute hydrochloric acid is added to neutralize the catalyst. After filtering the mixed solution, the catalyst, solvent, and excess reactants are removed by rotary evaporation to obtain a colloidal branched polymer B. The glass transition temperature of the polymer B is -30°C.
[0064] The polymer B and the LiFSI salt were mixed in a ratio of 100:40, and all the lithium salt was dissolved in the polymer at 80° C. to obtain the final hyperbranched polymer binder.
[0065] Comparative Example 1
[0066] This comparative example discloses a method for preparing a positive electrode by a PTFE dry process:
[0067] The fiberizable binder PTFE, the lithium cobalt oxide positive electrode material and the oxide solid electrolyte LATP were mixed in a volume ratio of 8:65:27 using a V-type mixer and stirred at 5 degrees Celsius for 2 hours.
[0068] The mixture is then passed through a high-speed air flow pulverizer to initially stretch and extend the binder PTFE in the material to obtain a pre-fiberized positive electrode mixture.
[0069] The pre-fiberized positive electrode mixture is calendered multiple times at 100-110 degrees Celsius on a dry electrode calendering device and then composited on an aluminum foil to obtain a PTFE dry positive electrode sheet.
[0070] The thickness of the solid positive electrode sheet is 100um and the surface density is 38mg / cm 2 , compacted density 3.7g / cm 3 , the porosity is 11.5%.
[0071] Example 3
[0072] This embodiment discloses a method for preparing a positive electrode sheet, the process flow is as follows: Figure 3 As shown:
[0073] The hyperbranched polymer binder prepared in Example 1, the lithium cobalt oxide positive electrode material and the oxide solid electrolyte LATP were put into an internal mixer in a volume ratio of 8:65:27, and the mixture was sheared and stirred at 80° C. to obtain a uniform positive electrode mixture.
[0074] The positive electrode mixture is put into a screw extruder, the operating temperature of each section of the screw extruder is above 80°C, the mixture is extruded through a 150um slit die, and directly compounded onto the current collector aluminum foil to obtain an uncalendered positive electrode.
[0075] The unrolled positive electrode is hot pressed at 60°C to the target thickness, and the positive electrode material is closely attached to the current collector. The final solid positive electrode sheet can be obtained. The solid positive electrode sheet has a thickness of 100um and a surface density of 40mg / cm 2 , compacted density 4.0g / cm 3 , the porosity is 4.3%. Its structural diagram is shown in Figure 4 As shown in FIG. 1 , 101 is a lithium cobalt oxide mixture and 102 is an aluminum foil current collector. The scanning electron microscope image is shown in FIG. Figure 5 As shown, compared with Comparative Example 1, the porosity of the electrode obtained by this method is 7% lower.
[0076] Example 4
[0077] This embodiment discloses a method for preparing a negative electrode sheet:
[0078] The following production conditions require production in a dry environment with a dew point below -60°C throughout the entire process due to the use of sulfide solid electrolyte LGPS.
[0079] The hyperbranched polymer binder, graphite negative electrode material, sulfide solid electrolyte LGPS and conductive carbon nanotubes prepared in Example 1 were put into an internal mixer in a volume ratio of 7:65:25:3, and the mixture was sheared and stirred at 80° C. to obtain a uniform negative electrode mixture.
[0080] The negative electrode mixture is put into a screw extruder, the operating temperature of each section of the screw extruder is above 80°C, the mixture is extruded through a 200um slit die, and directly compounded onto the carbon-coated copper foil of the current collector, and a release film is attached to the upper side to form an uncalendered negative electrode.
[0081] The unrolled negative electrode is hot pressed at 50°C to the target thickness, and the negative electrode material is closely attached to the carbon-coated copper foil current collector. After the product is stored in a -40°C environment, the release film is torn off to obtain the final solid negative electrode sheet. The solid negative electrode sheet has a thickness of 121um and a surface density of 23.5mg / cm 2 , compacted density 1.94g / cm 3 , the porosity is 3.3%.
[0082] Example 5
[0083] This embodiment discloses a method for preparing a double-sided negative electrode sheet:
[0084] The following production conditions require production in a dry environment with a dew point below -60°C throughout the entire process due to the use of sulfide solid electrolyte LGPS.
[0085] The hyperbranched polymer binder, graphite negative electrode material, sulfide solid electrolyte LGPS, plasticizer TEP and conductive carbon nanotubes prepared in Example 1 were put into an internal mixer in a volume ratio of 8:60:29:2:1, and the mixture was sheared and stirred at 80°C to obtain a uniform negative electrode mixture.
[0086] The negative electrode mixture is put into a screw extruder, the operating temperature of each section of the screw extruder is above 80°C, the mixture is extruded through a 200um slit die, and the extruded sheet, the carbon-coated copper foil current collector and the release film are stacked in the order of release film-negative electrode material-carbon-coated copper foil current collector-negative electrode material-release film to obtain an uncalendered double-sided negative electrode sheet.
[0087] The uncalendered double-sided negative electrode sheet is hot-pressed to the target thickness at 50°C, so that the negative electrode material and the carbon-coated copper foil current collector are closely attached. After the product is stored in a -40°C environment, the release films on both sides are torn off to obtain the final double-sided solid negative electrode sheet.
[0088] Its structural diagram is as follows Figure 6 As shown, 100 is a release film, 103 is a graphite mixture, and 104 is a carbon-coated copper foil current collector.
[0089] Example 6
[0090] This embodiment discloses a method for preparing a solid electrolyte membrane:
[0091] The following production conditions require production in a dry environment with a dew point below -60°C throughout the entire process due to the use of sulfide solid electrolyte LGPS.
[0092] The hyperbranched polymer binder and the sulfide solid electrolyte LGPS prepared in Example 1 were put into an internal mixer at a volume ratio of 5:95, and the mixture was sheared and stirred at 80° C. to obtain a uniform solid electrolyte mixture.
[0093] The solid electrolyte mixture is put into a screw extruder. The operating temperature of each section of the screw extruder is above 80°C. The mixture is extruded through a 100um slit die. Release films are attached to the upper and lower sides to form an uncalendered solid electrolyte membrane.
[0094] The uncalendered solid electrolyte membrane is hot pressed at 80°C to the target thickness. After the product is stored in a -40°C environment, the release films on both sides are torn off to obtain the final solid electrolyte membrane. The solid electrolyte membrane thickness is 40um and the compaction density is 1.93g / cm 3 , porosity 2.5%. The schematic diagram of the structure of the obtained LGPS solid electrolyte membrane is shown in Figure 7 As shown, 100 is a release film, 105 is a LGPS mixture; the EIS AC impedance diagram of the LGPS solid electrolyte membrane is as follows Figure 8 shown.
[0095] Comparative Example 2
[0096] This comparative example discloses a method for preparing a PTFE dry solid electrolyte membrane:
[0097] In a dry environment with a dew point below -60°C, the fiberizable binder PTFE and the sulfide solid electrolyte LGPS were stirred and mixed in a volume ratio of 5:95 using a V-type mixer at 5°C for 2 hours.
[0098] The mixture is then passed through a high-speed air flow mill to initially stretch and extend the binder PTFE in the material to obtain a pre-fiberized solid electrolyte mixture.
[0099] The pre-fiberized positive electrode mixture is subjected to multiple calendering processes at 100-110 degrees Celsius on a dry electrode calendering device to obtain a LGPS solid electrolyte membrane.
[0100] The solid electrolyte membrane has a thickness of 35um and a compaction density of 1.80g / cm 3 , porosity is 9.0%, and the tested ion conductivity is 0.5mS / cm.
[0101] Example 7
[0102] This embodiment discloses a method for preparing a solid electrolyte membrane:
[0103] The following production conditions require production in a dry environment with a dew point below -60°C throughout the entire process because of the use of sulfide solid electrolyte LPSC.
[0104] The hyperbranched polymer binder and the sulfide solid electrolyte LPSC prepared in Example 1 were put into an internal mixer at a volume ratio of 10:90, and the mixture was sheared and stirred at 80° C. to obtain a uniform solid electrolyte mixture.
[0105] The solid electrolyte mixture is put into a screw extruder, the operating temperature of each section of the screw extruder is above 80°C, the mixture is extruded through a 100um slit die, and after extrusion, it is quickly cooled and formed through an air outlet to obtain an uncalendered solid electrolyte membrane with a thickness of about 100um.
[0106] The uncalendered solid electrolyte membrane is hot pressed at 80°C using a surface ceramic coating roller to obtain the final solid electrolyte membrane when pressed to the target thickness. The solid electrolyte membrane thickness is 35um and the compaction density is 1.88g / cm 3 , porosity 2.4%, ion conductivity 1.9 mS / cm. Compared with Comparative Example 2, the porosity of the obtained solid electrolyte membrane is 6.6% lower and the ion conductivity is 4 times higher.
[0107] Comparative Example 1 Example 3 Comparative Example 2 Example 7 Compacted density <![CDATA[3.70g / cm 3 ]]> <![CDATA[4.02g / cm 3 ]]> <![CDATA[1.80g / cm 3 ]]> <![CDATA[1.88g / cm 3 ]]> Porosity 11.5% 4.3% 9.0% 2.4%
[0108] Example 8
[0109] This embodiment discloses a method for preparing a positive electrode & solid electrolyte membrane:
[0110] The following production conditions require production in a dry environment with a dew point below -60°C throughout the entire process because of the use of sulfide solid electrolyte LPSC.
[0111] The hyperbranched polymer binder, sulfide solid electrolyte LPSC and plasticizer TEP prepared in Example 1 were put into an internal mixer in a volume ratio of 5:92:3, and the mixture was sheared and stirred at 80° C. to obtain a uniform solid electrolyte mixture.
[0112] The above-mentioned solid electrolyte mixture is put into a screw extruder, and the operating temperature of each section of the screw extruder is above 80°C. The mixture is extruded through a 100um slit die and directly compounded onto the uncalendered solid positive electrode sheet in Example 3, and a release film is attached to the other side to form an uncalendered positive electrode & solid electrolyte membrane.
[0113] The above-mentioned complex is hot pressed at 80°C to the target thickness. After the product is stored in a -40°C environment, the release film is torn off to obtain the positive electrode & solid electrolyte membrane complex. Among them, the solid electrolyte membrane thickness is 30um, and the solid positive electrode thickness is 100um.
[0114] Comparative Example 3
[0115] This comparative example discloses a method for preparing a PTFE dry-process all-solid-state battery:
[0116] The PTFE dry electrode prepared in Comparative Example 1, the PTFE solid electrolyte membrane prepared in Comparative Example 2 and the lithium indium negative electrode sheet were assembled into an all-solid-state lithium battery. The all-solid-state lithium battery was hot pressed at 100 MPa for 1 h at 80°C to make the interface contact more compact. The all-solid-state battery was subjected to 0.1C / 0.1C charge and discharge cycles at room temperature, and the capacity remained 80% after 100 cycles.
[0117] Example 9
[0118] This embodiment discloses a method for preparing a solid-state lithium battery:
[0119] The hyperbranched binder dry-process positive electrode sheet prepared in Example 3, the solid electrolyte membrane prepared in Example 7 and the lithium-indium alloy negative electrode are assembled into an all-solid-state lithium battery. The assembled battery is hot-pressed at 20 MPa for 1 h at 30-40°C to make the interface contact more compact, thereby obtaining a solid-state lithium battery. Fig. 9 As shown, the solid-state battery was subjected to 0.1C / 0.1C charge-discharge cycles at room temperature, and the capacity retention rate after 500 cycles was 84%, with no dendrite penetration. Compared with Comparative Example 3, the all-solid-state lithium battery of this embodiment has higher charge-discharge capacity and better cycle performance.
Claims
1. A method for preparing a solid electrolyte membrane, characterized in that: The steps include: (1) adding a solid electrolyte material, a polymer binder and a plasticizer into a mixer in proportion, and obtaining a uniform mixture by high-temperature mixing, wherein the solid electrolyte material accounts for 85% to 98% by volume; the polymer binder accounts for 2% to 10% by volume; the plasticizer accounts for 0% to 5% by volume; and the glass transition temperature of the polymer binder is lower than -30°C; (2) extruding the mixture through a screw and then rapidly cooling it to obtain an independent self-supporting solid electrolyte membrane; the extrusion temperature is not less than 80° C., and the product porosity is less than 5%; The solid electrolyte material includes but is not limited to polyethylene oxide PEO, lithium lanthanum zirconium oxide LLZO, lithium germanium phosphorus sulfur LGPS and lithium indium chloride Li3InCl6; The polymer binder is a hyperbranched functional polymer, which is prepared by the following steps: Step 1: using a raw material with multiple nucleophilic sites to react with a crosslinking agent to generate a branched donor polymer; Step 2: The nucleophilic site of the donor polymer undergoes a Michael addition reaction to obtain a hyperbranched polymer; Step 3: heating and mixing the hyperbranched polymer and the metal salt at 40° C. until the salt is completely dissociated, to obtain; The raw materials in step 1 are one or more of polyols, 2,3-dimercaptopropanol, sorbitol, pentaerythritol, inositol, dipentaerythritol, pentaerythritol, amino alcohol, polyethyleneimine, cysteine, and dithiothreitol; The cross-linking agent is dialdehyde, epichlorohydrin, diisocyanate, diacrylate, diglycidyl ether, dibromide or dichloride; The metal salt added in step 3 is one or more of lithium salt, sodium salt, magnesium salt and aluminum salt.
2. A method for preparing a solid-state battery electrode, characterized in that: The steps include: (1) adding an electrochemical functional material, a polymer binder and a plasticizer into a mixer in proportion, and obtaining a uniform mixture by high-temperature mixing, wherein the volume proportion of the electrochemical functional material is 83%-98%; the volume proportion of the polymer binder is 2%-10%; the volume proportion of the plasticizer is 0%-5%; and the glass transition temperature of the polymer binder is lower than -30°C; (2) Extruding the above-mentioned mixed material into sheets through a screw, compounding it on a current collector and calendering to obtain a final product; wherein the extrusion temperature is not less than 80° C. and the porosity of the product is less than 5%; Electrochemical functional materials include solid electrolyte materials, positive and negative electrode active materials and conductive materials; The positive and negative electrode active materials include lithium ion battery positive electrode materials, sodium ion battery positive electrode materials, lithium battery negative electrode materials and sodium battery negative electrode materials; The conductive material is any one or more of conductive carbon black, graphene, and carbon nanotubes; The polymer binder is a hyperbranched functional polymer, which is prepared by the following steps: Step 1: using a raw material with multiple nucleophilic sites to react with a crosslinking agent to generate a branched donor polymer; Step 2: The nucleophilic site of the donor polymer undergoes a Michael addition reaction to obtain a hyperbranched polymer; Step 3: heating and mixing the hyperbranched polymer and the metal salt at 40° C. until the salt is completely dissociated, to obtain; The raw materials in step 1 are one or more of polyols, 2,3-dimercaptopropanol, sorbitol, pentaerythritol, inositol, dipentaerythritol, pentaerythritol, amino alcohol, polyethyleneimine, cysteine, and dithiothreitol; The cross-linking agent is dialdehyde, epichlorohydrin, diisocyanate, diacrylate, diglycidyl ether, dibromide or dichloride; The metal salt added in step 3 is one or more of lithium salt, sodium salt, magnesium salt and aluminum salt.
3. The method according to claim 1 or 2, characterized in that: The plasticizer is TEP, DOP or BET.
4. The method according to claim 2, characterized in that: The positive electrode material of the lithium ion battery is LiMn2O4, LiCoO2, LiFePO4, LiNi x Co y Mn z O2、LiNi x Co y Al z One or more of O2 and lithium-rich compounds, wherein x+y+z=1; The positive electrode material of the sodium ion battery is one or more of sodium metal oxide, Prussian material, and polyanion compound; The negative electrode material of the lithium battery is one or more of graphite, silicon, lithium titanate, silicon dioxide, tin, indium, and hard carbon; The negative electrode material of the sodium battery is one or more of graphite, soft carbon, hard carbon, and transition metal oxides; When manufacturing the positive electrode sheet, the substrate current collector is a perforated aluminum foil, a carbon-coated aluminum foil or a composite aluminum foil; when manufacturing the negative electrode sheet, the substrate current collector is a perforated copper foil, a composite copper foil or a carbon-coated copper foil.
5. The method according to claim 2, characterized in that: When preparing the positive and negative electrodes of solid-state batteries, the volume of positive and negative active materials accounts for 60%-75%; the volume of solid electrolyte materials accounts for 23%-38%; the volume of conductive agents accounts for 0%-5%; the volume of polymer binders accounts for 2%-10%; and the volume of plasticizers accounts for 0%-5%.
6. An electrochemical device, characterized in that: A solid electrolyte membrane or a solid battery electrode prepared by the method according to any one of claims 1 to 5.
Citation Information
Patent Citations
In-situ preparation method of dry-method electrode membrane and dry-method electrode thereof
CN114171710A
Dry electrode preparation method, battery and dry electrode preparation device
CN116706074B
Method for preparing dry-method electrode, obtained dry-method electrode and application
CN116960285A
Dry-method electrode and preparation method thereof
CN117154005A
Dry-method battery diaphragm and preparation method thereof, pole piece and battery
CN116598431A